2021
DOI: 10.1002/suco.202000029
|View full text |Cite
|
Sign up to set email alerts
|

Building information modeling and artificial intelligence: Advanced technologies for the digitalisation of seismic damage in existing buildings

Abstract: This research, which is based on the digital technologies building information modeling (BIM) and artificial intelligence, describes achievements in the field of detecting, assessing, and digitalising damage in existing buildings. The purpose of the study is to highlight the potential and current benefits of combining structural‐assessment methods with the automatic digitisation of hazard‐induced damage in affected buildings. To this end, the aforementioned technologies are employed in the form of an image‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
1
18
0
4
Order By: Relevance
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed that in addition to the concentration of chloride ions, increasing the temperature also significantly reduces the chloride ions penetration resistance. [30][31][32] The use of artificial intelligence in the field of civil engineering [33][34][35][36][37][38][39][40][41][42][43][44] today more than ever is being considered. 45 The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…As a 3D model containing lifecycle building information, BIM has also been widely used for managing inspection data. There are mainly three methods: 1) linking inspection data to BIM; 2) voxel BIM for building visual inspection (31) Inspection data management (23) Inspection data collection and management (1)…”
Section: Bim For Visual Building Inspectionmentioning
confidence: 99%
“…Note: the number in the parenthesis is the number of existing studies IOP Publishing doi:10.1088/1755-1315/1101/6/062030 6 representation in BIM; 3) texturing images into BIM. Most of the current efforts (19 out of 23 articles) directly linked the inspection data to BIM, such as (1) linking images and corresponding damage information to BIM components [29]; (2) inserting inspection reports into BIM [30]; (3) colouring components in BIM to represent the damage level [31]. The component condition rating was further achieved based on the documented damage information by fuzzy logic [32] and pre-defined rules [33].…”
Section: Inspection Path Planning (1) Inspection Data Collection (1)mentioning
confidence: 99%
“…Reem et al [27] developed a novel method for leveraging laser scanning technology to generate a BIM model of earthquake loss based on existing BIM models. Musella et al [28] applied BIM and artificial intelligence technology to the seismic damage evaluation of existing buildings, in which the graphic recognition and classification technology was applied to obtain the building visual damage data. e method provided a new way for evaluating, designing, and managing the seismic repair process of existing buildings.…”
Section: Introductionmentioning
confidence: 99%